RIGHTS PROTECTION EVOLVEMENT IN POLISH JUDICIAL PROCEEDINGS - NEW SEPARATE PROCEEDINGS - Zembrzuski, Tadeusz (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
In recognition of the concept of consumer rights to trial, individual and collective consumer rights should be extended across Europe as well as nationally. The need to affirm the processual position of so-called vulnerable parties in civil law proceedings is a matter as complex as it is multifaceted. The Polish legislator having devised new separate proceedings for cases involving consumers is a manifestation of the equalising justice principle having been realised. Regardless, one may well doubt whether the current procedural form comprises a sufficient volume of significant deviations from ordinary proceedings to justify such nature to be conferred upon it. Related deliberations form part of a broader discussion regarding the structure, form, and suitability of Polish procedural law.
Keywords: consumer; protection of consumer rights; consumer access to justice; civil law; civil proceedings; special proceedings